Characterisation of novel Burkholderia isolates associated with the Leguminosae - Walker, Robert Malcolm (Curtin University, 2013)
This study examined fourteen plant-associated Burkholderia species collected from South America, South Africa and Australia. Phylogenetic analysis indicates that the genus Burkholderia contains two lineages, one group are primarily pathogens, the second are plant growth promoting and environmental species. Most nodulated Australian legumes and Mimosa pudica and demonstrated plant growth promoting properties and had no pathogenic activity on Caenorhabditis elegans. Separation of intact genomic DNA indicated that all species contain a large secondary chromosome.